Dietary practices of South African ultradistance runners - Peters, E. M.; Goetzsche, J. M. (International Journal of Sport Nutrition and Exercise Metabolism, 1997)
Training (T) and prerace (PR) dietary intakes of male and female athletes participating in a 90-km ultramarathon and the usual diets of matched, sedentary controls were investigated using 24-hr dietary records. Supplement use, mean weekly training distance, and race performance times were recorded. Macro- and micronutrient intakes were analyzed using computerized nutritional analysis programs. Total mean energy intake in the T and PR diets of the runners was 10.1 and 12.8 MJ in the men (n = 150) and 7.5 and 9.1 MJ in the women (n = 23). Mean relative contribution of CHO to the runners' total kilojoule intake increased from 50.0 and 49.5% in the T diets to 57.7 (p < .05; n = 153) and 56.4% (p < .05; n = 23) in the PR diets of male and female runners, respectively, and energy-boosting supplements were included in the PR diets of 48% of female and 59% of male runners. Seventy-eight percent of female and 62% of male runners used vitamin and mineral supplements in their T diets as opposed to 39% of female and 28% of male controls. No statistically significant relationship was found between total kilojoule, CHO, fat, protein, and selected micronutrient intake during the 3 days before the race and performance in the 90-km event in runners of homogenous training status and gender.